Empowerment of the Lentora Turtle Care Group in Mapane Tambu Village, Balaesang District, Donggala Regency - Suparman, Suparman; Paembonan, Laendatu; Tallesang, Mukhtar; Jaya, Andi Herman; Syatir, Ahmad; Suirlan, Rita (Universitas Serang Raya, 2025)
The Mapane Tambu Village community group has long pursued Lentora Turtle Conservation. However, these conservation activities still have various obstacles to their implementation, especially in the buildings and infrastructure that support the conservation of Lentora turtles. These obstacles are related to funding problems, which are permanent in nature. The long-term existence of Lentora turtle conservation can benefit the people of Mapane Tambu Village if it is managed well, especially if it is used as a turtle conservation ecotourism area. Low public awareness and knowledge and a lack of concern for turtle conservation are the main problems in turtle conservation activities. This service aims to help empower the Lentora Turtle Care Group to raise funds for the Mapane Tambu Village, Balaesang District, Donggala Regency community. The stages of this service activity include preparation and implementation (training and socialization). The achievement of the service was an increase in donors for turtle conservation fundraising from 4 donors to 6 donors. The Lentora turtle care group initially had problems providing turtle food, but through this service, it was able to obtain permanent donors to provide lentora turtle food. Furthermore, the sustainability of community service activities requires assistance in developing turtle conservation ecotourism as a new business opportunity to increase additional income and as a new source of Village Original Income through the tourism sector.